2013
DOI: 10.21109/kesmas.v7i10.4
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko Kematian Ibu

Abstract: AbstrakAngka Kematian Ibu (AKI) di Kabupaten Pati bergerak fluktuatif dan menunjukkan status tertinggi pada tahun 2011 dengan 126 per 100.000 kelahiran hidup. Tujuan penelitian ini adalah menggambarkan kematian ibu di Kabupaten Pati dan menganalisis faktor risiko kematian maternal di Kabupaten Pati Tahun 2011. Penelitian menggunakan pendekatan observasional analitik dengan metode kasus kontrol. Jumlah sampel adalah 24 untuk setiap kelompok kasus dan kelompok kontrol. Analisis data menggunakan uji univariat, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
1
25

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 2 publications
5
14
1
25
Order By: Relevance
“…The results in this study are in accordance to a study by Aeni (2013), which show that the complication that occurs during the pregnancy and the parturition has significant relationship to the improvement on the risk of maternal mortality. Most complications occur during the parturition and the postpartum period, which lead to maternal mortality (Weyesa et al, 2015).…”
Section: The Influence Of Obstetric Complication On the Maternal Mortsupporting
confidence: 92%
“…The results in this study are in accordance to a study by Aeni (2013), which show that the complication that occurs during the pregnancy and the parturition has significant relationship to the improvement on the risk of maternal mortality. Most complications occur during the parturition and the postpartum period, which lead to maternal mortality (Weyesa et al, 2015).…”
Section: The Influence Of Obstetric Complication On the Maternal Mortsupporting
confidence: 92%
“…1 Maternal mortality rate (MMR) and infant mortality rate (IMR) are highest in developing countries. Mortality and morbidity among pregnant and birth-giving women are thus significant issues in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that late decision-making factors, late arrivals and late delivery of services in health facilities were the main factors of maternal deaths. This can happen as a result of the mother's reluctance to get to the health facility immediately because she believes that the signs of complications are common in pregnancy, while other family members are unaware of the obstetric obstacles [9]. The literature review indicates that the increase in maternal mortality is caused by 3 delays.…”
Section: Resultsmentioning
confidence: 99%